Fatal Systemic Toxoplasmosis by a Novel Non-archetypal Toxoplasma gondii in a Bryde’s Whale (Balaenoptera edeni) - Díaz-Delgado, Josué; Groch, Kátia R.; Ramos, Hernani G. C.; Colosio, Adriana Castaldo; Alves, Bruna Farias; Pena, Hilda F. J.; Catão-Dias, José L. (Frontiers in Marine Science, 2020)
We report the results of pathological, immunohistochemical and molecular genotyping analyses in a Bryde's whale (Balaenoptera edeni) with disseminated toxoplasmosis. A 10.7 m-long, adult, male Bryde's whale in poor body condition stranded alive in August 21st, 2018, in ‘Pontal do Ipiranga’, Linhares, Espirito Santo state (Brazil). The animal died shortly after stranding and was promptly autopsied. The main gross findings were: diffuse axial skeletal muscle atrophy; generalized congestion, petechiation and ecchymoses; necrotizing splenitis, hepatitis, myocarditis, pneumonia and lymphadenitis (prescapular, pulmonary, mediastinal, mesenteric); bilateral scapulohumeral hemarthros; and severe pulmonary edema. Microscopic examination confirmed the aforementioned diagnoses, featuring a histopathologic signature characterized by multisystemic necrotizing inflammation with vasculitis and disseminated intravascular coagulation, thrombosis and numerous intralesional protozoal cysts and extracellular tachyzoites morphologically compatible with Toxoplasma gondii. Immunohistochemical and polymerase chain reaction (PCR) analysis targeting a repetitive 529 bp DNA fragment of T. gondii confirmed toxoplasmosis in the liver, spleen, lung and lymph nodes. PCR-restriction fragment length polymorphism (RFLP) analysis using 11 markers identified a new non-archetypal genotype, ToxoDB-RFLP genotype #300. Further, the genotyping by microsatellite technique employed 15 markers and confirmed a unique non-archetypal T. gondii strain, designated PS-TgBaledBrES1. These novel results add to the diversity of this parasite in the world and to the scarce data on T. gondii genotype distribution in cetaceans, represent the first record of toxoplasmosis in a Bryde's whale and set the baseline knowledge for future research on T. gondii genotyping research in marine mammals from South America.